2016
DOI: 10.1016/j.kint.2016.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Zeb2 in mesenchyme-derived nephrons causes primary glomerulocystic disease

Abstract: Primary glomerulocystic kidney disease is a special form of renal cystic disorder characterized by Bowman’s space dilatation in the absence of tubular cysts. ZEB2 is a SMAD-interacting transcription factor involved in Mowat-Wilson syndrome, a congenital disorder with an increased risk for kidney anomalies. Here we show that deletion of Zeb2 in mesenchyme-derived nephrons with either Pax2-cre or Six2-cre causes primary glomerulocystic kidney disease without tubular cysts in mice. Glomerulotubular junction analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that ZEB2 expression promotes epithelial-to-mesenchymal transition (EMT) in renal cell carcinoma (RCC) and accumulated ZEB2 is an effective biomarker for the poor prognosis of patients with RCC [51]. Additionally, mice with a ZEB2specific deletion in metanephric mesenchyme led to primary glomerulocystic disease without tubular dilatation, which was absent in control mice, suggesting ZEB2 is required for proximal tubule development and normal glomerulotubular junction formation [52]. microRNAs have been found to be a regulator of ZEB2 and function as the EMT suppressor in many types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ZEB2 expression promotes epithelial-to-mesenchymal transition (EMT) in renal cell carcinoma (RCC) and accumulated ZEB2 is an effective biomarker for the poor prognosis of patients with RCC [51]. Additionally, mice with a ZEB2specific deletion in metanephric mesenchyme led to primary glomerulocystic disease without tubular dilatation, which was absent in control mice, suggesting ZEB2 is required for proximal tubule development and normal glomerulotubular junction formation [52]. microRNAs have been found to be a regulator of ZEB2 and function as the EMT suppressor in many types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…(B)Relative expression level of key marker genes as a function of pseudotime. zeb2 regulates mesenchymal progenitors in a variety of contexts(Hegarty et al, 2015;Rasouly et al, 2016;DaSilva-Arnold et al, 2019;Francescangeli et al, 2020). runx2 and sp7 regulate differentiation of amniote osteoblasts and odontoblasts(Jussila and Thesleff, 2012;Zhang, 2012;Bae et al, 2018).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that the genetic deletion of ZEB1 and ZEB2 (another Zeb family gene) in mice can lead to renal fibrosis in vitro and kidney disease, respectively. 25 , 32 Hence, we postulated that HG induces renal fibrosis by downregulating lnc ZEB1-AS1 to suppress ZEB1 expression.…”
Section: Discussionmentioning
confidence: 98%